2010
DOI: 10.4103/0974-9233.63072
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal worm and repeat laser photocoagulation

Abstract: Diffuse unilateral subacute neuroretinitis (DUSN) can be a diagnostic dilemma. Laser photocoagulation of the subretinal worm is an effective treatment for eradication. Early laser photocoagulation has been advocated. We report a case of a middle aged man who presented with decreased vision and a sub retinal macular worm that required two laser sessions for complete eradication of the worm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Natesh et al, reported a similar finding in their 2010 case report in which the nematode remained active post-laser treatment. 14 In their report, the nematode was determined to be alive when it moved away from the lasered area and was killed with subsequent laser treatment. In our case, the nematode carcass was present within the lasered area, but to definitively confirm the nematode was dead, we imaged the area several times, using MultiColor ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Natesh et al, reported a similar finding in their 2010 case report in which the nematode remained active post-laser treatment. 14 In their report, the nematode was determined to be alive when it moved away from the lasered area and was killed with subsequent laser treatment. In our case, the nematode carcass was present within the lasered area, but to definitively confirm the nematode was dead, we imaged the area several times, using MultiColor ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This method has proven to be very effective in treating "diffuse unilateral subacute neuroretinitis," a clinical entity caused by subretinal migration of various nematode larvae (including, e.g., Toxocara canis, Ancylostoma caninum, Strongyloides stercoralis, Ascaris lumbricoides, and Baylisascaris procyonis). 2 If surgery and laser photocoagulation are not indicated, available, or possible, treatment with antiparasitic drugs presents an alternative. Adjunctive corticosteroid treatment is used in the presence of an inflammatory reaction or to avert treatmentinduced inflammatory reactions triggered by antigen liberation due to dying parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Both oral anthelmintics and steroids have been shown to reduce inflammation and may be considered if no worm is found after careful examination. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%